Clinico-Genomic Analysis Reiterates Mild Symptoms Post-vaccination Breakthrough: Should We Focus on Low-Frequency Mutations? - Kanakan, Akshay; Mehta, Priyanka; Devi, Priti; Saifi, Sheeba; Swaminathan, Aparna; Maurya, Ranjeet; Chattopadhyay, Partha; Tarai, Bansidhar; Das, Poonam; Jha, Vinita; Budhiraja, Sandeep; Pandey, Rajesh (Frontiers in Microbiology, 2022)
Vaccine development against SARS-CoV-2 has been of primary importance to contain the ongoing global pandemic. However, studies have demonstrated that vaccine effectiveness is reduced and immune response is evaded by variants of concerns (VOCs) which include Alpha, Beta, Delta and the most recent, Omicron. Subsequently, several vaccine breakthrough infections have been reported among healthcare workers (HCWs) due to their prolonged exposure to viruses at healthcare facilities. We conducted a clinico-genomic study of ChAdOx1 (Covishield) vaccine breakthrough (VBT) cases in HCWs after complete vaccination. Based on the clinical data analysis, most of the cases were categorised as mild with minimal healthcare support requirements. These patients were divided into two sub-phenotypes based on symptoms, mild and mild plus. Statistical analysis showed a significant correlation of specific clinical parameters with VBT sub-phenotypes. Viral genomic sequence analysis of VBT cases revealed a spectrum of high and low frequency mutations. Deeper analysis revealed the presence of low-frequency mutations within the functionally important regions of SARS-CoV-2 genomes. Emphasising potential benefits of surveillance, low frequency mutations, D144H in the N gene and D138Y in the S gene, was observed to potentially alter protein secondary structure with possible influence on viral characteristics. Substantiated by literature, our study highlights the importance of integrative analysis of pathogen genomic and clinical data to offer insights into low frequency mutations that could be a modulator of VBT infections.